Investigation on Synthesis of Trimethylolpropane (TMP) Ester from Non-edible Oil - Nurazreen Shazwin Kamarudin; Harumi Veny; Nailah Fasihah Sidek; Faisal Abnisa; Rozana Azrina Sazali; Noorhaliza Aziz (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
Trimethylolpropane (TMP) ester is an eco-friendly lubricant that fully biodegradable and known as bio lubricant. In this study, TMP ester was produced from waste cooking oil and rubber seed oil through a two-step synthesis approach. The reaction is two stages transesterifications, in which the waste cooking oil and the rubber seed oil were first transesterified with methanol to produce methyl ester, followed by transesterification with TMP using para-Toluenesulfonic acid (p-TSA) as catalyst. Various effects of operating conditions were observed, such as reaction time, temperature and molar ratio of reactants. The TMP ester formation was determined based on the quantity of reactant conversion. The synthesized TMP ester was compared and characterized according to their properties. The results showed that the TMP ester from waste cooking oil (WCO) has shown better conversion compare to TMP ester from rubber seed oil (RSO), within a similar operating condition. The highest TMP ester conversion from WCO is 71%, at temperature of 150 ºC with molar ratio of FAME to TMP of 3:1 and catalyst amount of 2% (wt/wt). In addition, these polyol based esters from WCO and RSO exhibit appropriate basic properties for viscosity when compare with requirement standard of lubricant ISO VG46. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).